A comparative analysis of republican people’s party and republican reliance party: Similarities and difference - Alaçam, Müge (My University, 2011)
Cumhuriyet Halk Partisi ile Cumhuriyetçi Güven Partisi’nin Karşılaştırmalı Analizi: Benzerlikler ve Farklılıklar Bu tez, Cumhuriyetçi Güven Partisi ve 1992-sonrası Cumhuriyet Halk Partisi’nin parti programları, politik duruş ve söylemleri açısından karşılaştırmalı bir analizini sunmaktadır. İki farklı dönem ele alınarak yapılan bu analizde, ortanın solu ve demokratik sol politikaları ile 1992-sonrası Cumhuriyet Halk Partisi’nin politikaları arasında devamlılığın olup olmadığı ve CGP ile CHP arasındaki benzerlik ve farklılıkların ortaya konması amaçlanmıştır. İki partinin karşılaştırmalı analizi yapılırken, her iki partinin programları, önemli politik konular karşındaki söylem ve duruşları dikkate alınmıştır. İki parti arasındaki benzerlikler ve farklılıklar muhafazakâr cumhuriyetçi ideoloji çerçevesinde değerlendirilmiştir. Bu tezde CGP ve CHP’nin karşılatılmalı bir analizi yapılırken, Türk siyasal hayatında Cumhuriyetçi Güven Partisi’nin yeri, ideolojisi ve temel prensipleri ve 1992-sonrası CHP’nin ideolojisi ve politik söylemleri de ortaya konmaya çalışılmıştır. Cumhuriyetçi Güven Partisi, Cumhuriyet Halk Partisi, Ortanın Solu, Demokratik Sol, Muhafazakâr Cumhuriyetçilik

A Comparative Analysis of Republican People’s Party and Republican Reliance Party: Similarities and Differences This thesis presents a comparative analysis of the Republican Reliance Party and post-1992 Republican People’s Party in terms of their party programs, political stance and discourses. Taking two different periods into consideration in this analysis was aimed to clarify there was continuity or discontinuity between political line of left of center, democratic left politics and the post-1992 CHP, and similarities and differences between CGP and CHP. While studying comparative analysis between two parties, their party programs, discourses and attitudes toward significant political issues were taken into consideration. Similarities and differences between two parties were evaluated in the framework of conservative republican ideology. In this thesis, while a comparative analysis of the CHP and CHP was being presenting, the place, ideology and fundamental principles of the CGP in Turkish political life and the post-1992 CHP’s ideology and political discourses were also tried to clarify. Key Words: Republican Reliance Party, Republican People’s Party, Left of Center, Democratic Left, Conservative Republicanism
Keywords: Siyasi Partiler